PENGARUH METODE PEMBELAJARAN TUTOR SEBAYA TERHADAP KEMAMPUAN BOUNCE PASS PADA PEMBELAJARAN BOLA BASKET SISWA KELAS VII SMPN 117 JAKARTA TIMUR - Ihsan Suseno; Nana Suryana Nasution; Ardawi Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of peer tutoring on the ability to perform a bounce pass in basketball learning for seventh-grade students at SMPN 117 Jakarta Timur. The bounce pass technique is an essential skill in basketball, but many students struggle to master it. This is due to a lack of understanding of the mechanics of the movement and insufficient practice. Conventional teaching methods, which primarily rely on lectures and demonstrations, are considered less effective in improving students' skills. The research method used is a quasi-experimental design with a pretest-posttest one-group design. The study involved 35 seventh-grade students at SMPN 117 Jakarta Timur who received treatment using the peer tutoring method. The instrument used was a bounce pass skill test, measured before and after the intervention. Data analysis was performed using paired samples t-test to examine the difference in students' abilities before and after the peer tutoring method was applied. The results showed a significant improvement in students' bounce pass skills after the implementation of the peer tutoring method. The average improvement score was 4.689 points, with a significance value of p = 0.000. This indicates that the peer tutoring method effectively enhanced students' technical abilities in performing the bounce pass. Students felt more confident and active in the learning process due to the increased interaction with their peers. Based on the findings, it can be concluded that the application of the peer tutoring method has a positive impact on improving students' bounce pass skills. Therefore, it is recommended to implement this method in basketball learning to enhance students' basic motor skills.